2013
DOI: 10.1007/s00705-013-1904-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of porcine sapoviruses in pigs from the Amazon region of Brazil

Abstract: Sapoviruses (SaVs) belong to the family Caliciviridae and are related to gastroenteritis viruses of humans and animals. These agents have been reported from several countries of the world and represent an important cause of economic loss. The Amazon area has a high degree of diversity of animals and plants, is located in the Northern Region of Brazil and accounts for a large part of the Brazilian territory. In this study, stool samples were collected from pigs during the phase of nursing (less than 28 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the SaV‐positive pigs with clinical diarrhoea had significantly higher virus loads ( C t = 26.0 ± 0.5) compared to rRT‐PCR positive but clinically healthy pigs ( C t =33.2 ± 0.9, with 2 7 = 128‐fold difference in quantity). Most porcine SaVs have so far been reported from asymptomatic pigs and several studies reported no significant differences in the positive rates of porcine SaV between clinical and non‐clinical pigs (Barry et al., 2008; Collins et al., 2009; das Merces Hernandez et al., 2014; Dufkova et al., 2013; Mijovski et al., 2010; Reuter et al., 2010). Further, it has been suggested that testing for the presence of SaV may not provide significant diagnostic value (Salamunova et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the SaV‐positive pigs with clinical diarrhoea had significantly higher virus loads ( C t = 26.0 ± 0.5) compared to rRT‐PCR positive but clinically healthy pigs ( C t =33.2 ± 0.9, with 2 7 = 128‐fold difference in quantity). Most porcine SaVs have so far been reported from asymptomatic pigs and several studies reported no significant differences in the positive rates of porcine SaV between clinical and non‐clinical pigs (Barry et al., 2008; Collins et al., 2009; das Merces Hernandez et al., 2014; Dufkova et al., 2013; Mijovski et al., 2010; Reuter et al., 2010). Further, it has been suggested that testing for the presence of SaV may not provide significant diagnostic value (Salamunova et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sapoviruses can cause gastroenteritis in humans and animals (Oka et al., 2015). Porcine SaV was first identified by electron microscopy in the United States in 1980 in a mixed infection with other viruses (Saif et al., 1980) and since then, SaVs have been reported from both diarrhoeic and asymptomatic pigs (das Merces Hernandez et al., 2014; Wang et al., 2020; Wang et al., 2006). Experimental infection of cell culture‐adapted SaVs in gnotobiotic piglets successfully induced enteritis and diarrhoea (Flynn et al., 1988; Guo et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The viral infection was clarified to be the result of gastroenteritis in both humans and animals [ 30 ]. Later researchers reported PoSaV strains in diarrhoeic and asymptomatic pigs [ 36 , 37 ]. In experimental piglets, PoSaV strains that had been recovered from cell culture successfully established symptoms of diarrhea and enteritis in the infected pigs [ 11 , 38 ].…”
Section: Discussionmentioning
confidence: 99%